Effect of Therapeutic Ultrasound Augmented by Sacro-Iliac Belt and Core Strengthening Exercises on Sacro-Iliac Joint Pain after Delivery - Ahmed M. Shahein; Magda S. Morsy; Adel Farouk (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to investigate the effect of therapeutic ultrasound augmented by sacro-iliac belt and core strengthening exercises on sacro-iliac joint pain after delivery. Thirty multiparous women suffering from sacro-iliac joint pain for at least 3 months after delivery were participated in this study. They were selected randomly from the physical therapy department in police authority hospital in Al Agouza. All the women were randomly divided into two groups equal in number, study group (group A) and control group (group B). Study group (group A): It was consisted of 15 patients each patient received continuous ultrasound on two SIJs for ten minutes (5 minutes for each SIJ), 3 times/week for 4 weeks. Additionally, to this, she was asked to perform core strengthening exercises for 30 minutes, 3 times per week for 4 weeks. Also, each patient was advised to wear a sacro-iliac belt all the day and take it off only during sleep and taking a shower throughout the treatment course. Control group (group B): it was consisted of 15 patients asked to perform core strengthening exercises for 30 minutes, 3 times/week for 4 weeks and wear a sacro-iliac belt throughout the treatment course (4 weeks). All patients in both groups (A&B) were evaluated by visual analogue scale (VAS) and plasma cortisol level before starting and after the end of treatment program. The results showed a highly significant (P <0.001) decrease in VAS as well as plasma cortisol level after treatment program in both group, yet this decrease was more pronounced and statistically significant (P <0.001) in the study group when compared to the control group. It could be concluded that therapeutic ultrasound augmented by sacro-iliac belt and core strengthening exercises on sacro-iliac joint pain after delivery was more effective than core strengthening exercises augmented by sacro iliac belt.